Dung beetles of an Australian tropical savanna: Species composition, food preferences and responses to experimental fire regimes - Carvalho, Raquel L.; Weir, Tom; Vasconcelos, Heraldo L.; Andersen, Alan N. (Austral ecology, 2020)
Dung beetles are an ecologically important group of insects globally, but the ecology of the Australian fauna is poorly known. Here, we report on the first ecological study of dung beetles in an Australian tropical savanna, documenting species composition, food preferences and responses to fire. Dung beetles were baited using dung from five types of vertebrates as well as mushrooms. We sampled at nine plots subject to experimental fire regimes (three replicates each of high fire severity, moderate fire severity and unburnt over 15 years) at the Territory Wildlife Park near Darwin. Our samples were comprised entirely of nine native species of Onthophagus. Dog dung was the most attractive bait, recording all nine species and nearly 80% of all individuals, whereas no beetles were recorded at either wallaby or magpie‐goose dung. Dung beetle abundance was highest under high fire severity and was negatively correlated with the cover of woody vegetation, a result driven by the two most common species, O. minsiculus and O. nr. quadripunctulatus. Our results indicate that Onthophagus is the dominant genus in dung‐beetle assemblages of monsoonal Australia, as it is in open habitats of the Australian wet tropics. All our species of Onthophagus are relatively small (≤10 mm body length) and are ‘tunnellers’, storing dung and other food resources in tunnels dug immediately below the food source. Such an overwhelming dominance by small tunnellers does not occur in African savannas, reflecting the far lower availability of large mammalian dung in Australia.